Volume 2: Heat Transfer Enhancement for Practical Applications; Fire and Combustion; Multi-Phase Systems; Heat Transfer in Elec 2012
DOI: 10.1115/ht2012-58049
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation and Performance Evaluation of Isothermal Frictional Two Phase Pressure Drop Correlations in Vertical Downward Gas-Liquid Two Phase Flow

Abstract: The correct prediction of gas-liquid two phase pressure drop is of immense significance for proper sizing of industrial equipment and safety operations involved in chemical, energy and petrochemical applications. The hydrostatic component of the two phase pressure drop is predicted based on the accurate estimation of void fraction. However, there exists a complexity in correct estimation of the frictional component of two phase pressure drop owing to interfacial friction at dynamic gas-liquid interface. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…On the basis of the deviation of the two phase pressure drop from its single phase counterpart as shown in Figures 5-9, it is clear that the parameter that increases with increasing gas flow rate might correlate the two phase and single phase heat transfer coefficients. Bhagwat et al [12] found the non-dimensional frictional pressure drop defined by Equation (2) to increase with increasing superficial gas Reynolds number (Re sg ) and with the trend similar to that observed for two phase heat transfer. The major advantage of using this form of the correlation based on the Reynolds analogy is that it accounts for change in the flow condition such as the pipe diameter and fluid combination through the (φ) parameter.…”
Section: Reynolds Analogysupporting
confidence: 60%
See 2 more Smart Citations
“…On the basis of the deviation of the two phase pressure drop from its single phase counterpart as shown in Figures 5-9, it is clear that the parameter that increases with increasing gas flow rate might correlate the two phase and single phase heat transfer coefficients. Bhagwat et al [12] found the non-dimensional frictional pressure drop defined by Equation (2) to increase with increasing superficial gas Reynolds number (Re sg ) and with the trend similar to that observed for two phase heat transfer. The major advantage of using this form of the correlation based on the Reynolds analogy is that it accounts for change in the flow condition such as the pipe diameter and fluid combination through the (φ) parameter.…”
Section: Reynolds Analogysupporting
confidence: 60%
“…The problem with using Reynolds analogy is that it requires the frictional pressure drop data or a robust and accurate correlation to predict frictional pressure drop in different flow patterns. The isothermal frictional pressure drop data used to analyze Tang and Ghajar [1] correlation was obtained from the pressure drop measurements done by Bhagwat et al [12]. The Reynolds analogy given by Tang and Ghajar [1] is observed to predict the two phase convective heat transfer coefficient satisfactorily as shown in Figure 11.…”
Section: Reynolds Analogymentioning
confidence: 99%
See 1 more Smart Citation
“…In this case the friction factor is termed a two-phase friction factor and in reality, such methods are flow regime independent notably in the style of Lockhart -Martinelli (1949). The works of Klausner et al (1991), Dalkilic et al (2009) and Bhagwat et al (2012) are cases in point. Hewitt & Hall-Taylor (1970) have shown using the data of Gill et al (1964) that the homogeneous model method is less accurate than flow regime specific methods.…”
Section: Comparison Of Experimental Interfacial Friction Factor With mentioning
confidence: 97%